DNA barcodes and species distribution models evaluate threats of global climate changes to genetic diversity: a case study from Nanorana parkeri (Anura: Dicroglossidae). - Wei-wei Zhou; Bao-lin Zhang; Hong-man Chen; Jie-qiong Jin; Jun-xiao Yang; Yun-yu Wang; Ke Jiang; Robert W Murphy; Ya-ping Zhang; Jing Che (PLoS ONE, 2014)
Anthropogenic global climate changes are one of the greatest threats to biodiversity. Distribution modeling can predict the effects of climate changes and potentially their effects on genetic diversity. DNA barcoding quickly identifies patterns of genetic diversity. As a case study, we use DNA barcodes and distribution models to predict threats under climate changes in the frog Nanorana parkeri, which is endemic to the Qinghai-Tibetan Plateau. Barcoding identifies major lineages W and E. Lineage W has a single origin in a refugium and Lineage E derives from three refugia. All refugia locate in river valleys and each greatly contributes to the current level of intraspecific genetic diversity. Species distribution models suggest that global climate changes will greatly influence N. parkeri, especially in the level of genetic diversity, because two former refugia will fail to provide suitable habitat. Our pipeline provides a novel application of DNA barcoding and has important implications for the conservation of biodiversity in southern areas of the Qinghai-Tibetan Plateau.